THE NUMBER OF AVIATION SECURITY PERSONNEL ON SECURITY CHECK POINT 2 SERVICES - Nadia Ulhaq, Almira; Rochmawati, Laila; Muti Sazali, Abdul; Suryono, Wiwid (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2023)
Minangkabau International Airport is one of the air transportation gateways in Padang Pariaman Regency, West Sumatra. When the author conducted research during On the Job Training at Minangkabau International Airport, the author saw that the number of Aviation Security personnel at Security Check Point 2 was not in accordance with existing regulations. Effective and efficient security services at the airport are very important to maintain passenger safety and prevent threats to flight safety. One factor that affects the quality of security services is the number of personnel available to carry out security tasks at the Security Check Point. The purpose of this study was to determine the effect of the number of Aviation Security personnel on Security Check Point 2 services at Minangkabau International Airport which is important to support passenger safety and comfort and realize excellent service quality for Minangkabau International Airport. This research method uses a quantitative descriptive method by making observations at Minangkabau International Airport, then obtaining data by distributing questionnaires to organic Aviation Security Personnel and service users. The results of this study indicate that service users agree that the number of Aviation Security personnel affects service. The problems in this study are expected to be used to make policies in improving the quality of security services at the airport